Analisis Literature: Pengaruh AI-Based Feedback Terhadap Perkembangan Critical Thinking Skills Siswa Sekolah Menengah Pertama - Tika Mustika Sari; Siti Nurjanah, Syarifah; Ichsan Fauzi Rachman (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
. In the digital era, the use of Artificial Intelligence (AI) in education continues to expand, including its application in providing automated feedback to students. This study aims to systematically review the literature that examines the impact of AI-based feedback on the development of critical thinking skills among junior high school students. Using a narrative literature review approach, this paper analyzes relevant studies to identify patterns, key findings, and challenges in implementing AI in learning environments. The findings indicate that AI-based feedback has the potential to enhance students' critical thinking skills through timely, specific, and adaptive responses. However, challenges such as students’ dependency on technology and limited reflective engagement remain significant concerns. The teacher’s role remains essential in facilitating deep thinking processes and preventing passive use of AI. This review offers both theoretical and practical contributions to the development of technology-assisted learning that supports critical thinking skills at the junior high school level.